Kandungan nutrien, fraksi serat dan nutrient value fermentasi jerami kacang tanah (Arachys hypogaea) pada level nira lontar (Borassus flabellifer) yang berbeda - Wea, Redempta; Mangngi, Ria Yuniati Kana; Bay, Yovita Yuvensia; Badewi, Bachtaruddin; Semang, Agustinus; Koten, Bernadete Barek; Wirawan, I Gusti Komang Oka (Livestock and Animal Research, 2022)
Objective: Peanut straw is abundantly available and still contains the nutrients needed by livestock but has high crude fiber content. Therefore, it is processed using fermentation technology using palm sap. The nutrient content and fiber fraction of fermented peanut shells at different levels of palm sap is the aim of the research.Methods: The Completely Randomized Design (CRD) used with 4 treatments and 6 replications, namely: JKT0 = peanut straw without palm sap, JKT5 = peanut straw + 5% palm sap, JKT10 = peanut straw + 10% palm sap, JKT15 = peanut straw + 15% palm sap and fermented for 21 days. The research variables were nutrient content resulted of proximate analysis, fiber fraction, and nutrient value. The analysis used one-way variance and Duncan's Multiple Range Test (DMRT).Results: Increasing the use of palm sap up to 15% in rice straw fermentation led to a 15.59% decrease in dry matter, a 7.33% increase in nitrogen-free extract (BETN), a 19.67% decrease in ash, an increase of up to 6.13% of NDF, a decrease of 6 .99% ADF, 7.57% decrease in cellulose, 45.45% increase in hemicellulose, nutrient value (DMI, DMD, and RFV) but no effect on crude protein, crude fiber, crude fat and lignin. and the use of 10% palm sap gives optimal results.Conclusions: The fermentation process using palm sap affects the dry matter content, BETN, ash, NDF, ADF, hemicellulose, cellulose, but has no impact on the content of crude protein, crude fiber, crude fat, and lignin and the best palm sap level is 10%.